2007
DOI: 10.1002/pola.21897
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the sensitivity to acid inhibition in novel acrylates characterized by secondary functionalities

Abstract: Here we demonstrate that acrylates exhibit significant rate reductions in the presence of small concentrations of protic acids (0.1–0.5 wt %) compared with the bulk monomer concentration. Dramatically different sensitivities to acid inhibition, differing by up to 2 orders of magnitude, are exhibited for various acrylates. This study examines the various factors that cause enhanced sensitivity toward acid inhibition in novel acrylates characterized by carbamate and cyclic carbonate secondary functionalities. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Using a B3LYP/6-31G* basis they computed a negative charge for their modeled propagating radical, thus suggesting that the propagating species may have some negatively charged character. The anionic nature of the propagating species was further investigated by Bowman who found a significant inhibition by strong acid when polymerized under photoinitiated radical conditions [27]. Thus, it appears that there is a Michael addition component to the polymerization that is occurring at the acrylate functional group and this idea is supported by our findings.…”
Section: Tablesupporting
confidence: 59%
See 1 more Smart Citation
“…Using a B3LYP/6-31G* basis they computed a negative charge for their modeled propagating radical, thus suggesting that the propagating species may have some negatively charged character. The anionic nature of the propagating species was further investigated by Bowman who found a significant inhibition by strong acid when polymerized under photoinitiated radical conditions [27]. Thus, it appears that there is a Michael addition component to the polymerization that is occurring at the acrylate functional group and this idea is supported by our findings.…”
Section: Tablesupporting
confidence: 59%
“…That this is possible for the carbamate bearing monomers suggests that the descriptor functions to differentiate the faster carbamate acrylate monomers from the generally slower traditional acrylates. The importance of a contribution of electron density by the nitrogen to the carbamate carbonyl correlation speaks to the results of Kilambi for the acid inhibition of acrylates bearing novel functionalities, including carbamate and cyclic carbonate [27]. As the nitrogen of the carbamate donates electron density to the carbonyl group, the build-up of negative charge on the oxygen atom makes it a site for intermolecular hydrogen bonding, as well as a site for protonation under acidic conditions.…”
Section: Tablementioning
confidence: 95%
“…Recently a series of mono-vinyl (meth)acrylic monomers characterized by unique secondary moieties and greatly enhanced polymerization kinetics has been developed. The secondary moieties include, carbamates, carbonates, cyclic carbonates, cyclic acetals, hydroxyl/carboxy, oxazolidones, morpholine, and aromatic rings [11][12][13][14][15][16][17][18][19][20]. The cure rates of these mono-vinyl acrylates and methacrylates rival or exceed those of multifunctional acrylates while also achieving much higher extents of cure, hence reducing the amount of extractable material [13].…”
Section: Introductionmentioning
confidence: 99%
“…The exact reasons for the enhancement in reactivity have been elusive to date 3, 14–17. The copolymerization ratios of the acrylates with other monomers were observed to be altered upon incorporation of the secondary functionalities,18 and kinetic studies to investigate the mechanisms responsible for enhanced reactivity revealed that the addition of the secondary functionality alters the polymerization behavior by impacting the radical‐vinyl chemistry in these systems 18–20. A series of Michael addition reactions,21, 22 has previously been conducted on acrylic and methacrylic monomers incorporating carbamate, N ‐acyl carbamate, carbonate and cyclic carbonate functionalities 23.…”
Section: Introductionmentioning
confidence: 99%